Expanding a common metric for depression reporting: linking two scales to PROMIS® depression. - Kaat, Aaron J.; Newcomb, Michael E.; Ryan, Daniel T.; Mustanski, Brian (Quality of Life Research, 2017)
Purpose: Depression is a significant mental health concern. There are numerous depression questionnaires, several of which can be scored onto the Patient Reported Outcomes Measurement Information System (PROMIS®) Depression metric. This study expands the unified metric by linking depression subscales from the Adult Self-Report (ASR) and the Brief Symptom Inventory (BSI) to it.Methods: An online sample of 2009 men who have sex with men (MSM) was recruited. Item factor analysis was used to evaluate the dimensionality of the aggregated measures and confirm the statistical assumptions for linking. Then, linking was conducted using equipercentile and item response theory (IRT) methods. Equipercentile linking considered varying degrees of post-smoothing. IRT-based linking used fixed-anchor calibration and separate calibration with Stocking-Lord linking constants.Results: All three scales were broadly unidimensional. This MSM sample had slightly higher average depression scores than the general population (mean = 54.4, SD = 9.6). Both linking methods provided robust, largely comparable results. Subgroup invariance held for age, race, and HIV status. Given the broad comparability across methods, the crosswalk between raw sum scores and the unified T-score metric used fixed-anchor IRT-based methods.Conclusions: PROMIS provides a unified, interpretable metric for depression reporting. The results of this study allow the depression subscales from the ASR and BSI to be rescored onto the unified metric with reasonable caution. This will benefit epidemiological projects aggregating data across various measures or time points.